Pelatihan Edukasi Seksual untuk Ibu dalam Pencegahan Kekerasan Seksual Pada Anak Usia Dini di Kota Cirebon - Nurlina, Neli; Hapitria, Pepi (Universitas Galuh, 2025)
Early sex education is an important effort to prevent sexual violence against children. Mothers play a significant role as the first educators in the family; therefore, they need adequate knowledge and skills in providing sex education to young children. This community service activity, titled “Mother Care Training for the Prevention of Child Sexual Violence,” targeted mothers with children under six years old. The two-day training (approximately four hours per day) began with an assessment of participants’ knowledge and attitudes, followed by educational sessions using presentations, videos, and role play. The program concluded with a post-training evaluation and the development of follow-up plans. The results showed an increase in average maternal knowledge from 19.17 to 21.75 and an increase in attitudes from 76.17 to 21.75. Moreover, participants became more empowered to share the information with other mothers. It is recommended that health centers integrate child sexual violence prevention efforts into existing programs and implement routine educational activities in schools and communities.